A lattice Boltzmann investigation of steady-state fluid distribution, capillary pressure and relative permeability of a porous medium: Effects of fluid and geometrical properties. (June 2018) - Li, Zi; Galindo-Torres, Sergio; Yan, Guanxi; Scheuermann, Alexander; Li, Ling
Highlights: Simultaneous steady-state two-phase flow simulations were conducted, and implied the ways to improve the macroscopic flow equation. The adhesive fluid–solid interaction provided another source of capillary pressure. Large adhesive strength and fine pores enhanced the film fluid effect. The NP and WP fluids were both subjected to the capillary resistance. Decreased wettability, large average pore radius and improved fluid connectivity alleviated the capillary pressure effect. Abstract: Simulations of simultaneous steady-state two-phase flow in the capillary force-dominated regime were conducted using the state-of-the-art Shan–Chen multi-component lattice Boltzmann model (SCMC-LBM) based on two-dimensional porous media. We focused on analyzing the fluid distribution (i.e., WP fluid-solid, NP fluid-solid and fluid-fluid interfacial areas) as well as the capillary pressure versus saturation curve which was affected by fluid and geometrical properties (i.e., wettability, adhesive strength, pore size distribution and specific surface area). How these properties influenced the relative permeability versus saturation relation through apparent effective permeability and threshold pressure gradient was also explored. The SCMC-LBM simulations showed that, a thin WP fluid film formed around the solid surface due to the adhesive fluid-solid interaction, resulting in discrete WP fluid distributions and reduction of the WP fluid mobility. Also, the adhesive interaction provided another source of capillary pressure in addition to capillary force, which, however, did not affect the mobility of the NP fluid. The film fluid effect could be enhanced by large adhesive strength and fine pores in heterogeneous porous media. In the steady-state infiltration, not only the NP fluid but also the WP fluid were subjected to the capillary resistance. The capillary pressure effect could be alleviated by decreased wettability, large average pore radius and improved fluid connectivity in heterogeneous porous media. The present work based on the SCMC-LBM investigations elucidated the role of film fluid as well as capillary pressure in the two-phase flow system. The findings have implications for ways to improve the macroscopic flow equation based on balance of force for the steady-state infiltration.